Silicon-based nanosphere anodes for lithium-ion batteries: Features, progress, effectiveness, challenges, and prospects - Hossain M.A.M.; Hannan M.A.; Ker P.J.; Tiong S.K.; Salam M.A.; Abdillah M.; Mahlia T.M.I. (Elsevier Ltd, 2025)
Lithium-ion batteries are essential for powering various technologies, including portable electronics, electric vehicles, and renewable energy systems. Silicon anodes, with their significantly higher theoretical capacity compared to standard graphite anodes, have emerged as an important focus in battery development. However, their implementation faces challenges mainly because of the volume expansion that occurs during charging, resulting in mechanical strain and reduced capacity over time. Silicon-based nanospheres have been identified as a promising solution to overcome these issues because of their improved structural stability and electrochemical performance. This study explores the innovative fabrication approaches, progress, electrochemical behavior, and effectiveness of silicon-based nanosphere anodes, emphasizing their critical role in the advancement of battery technologies. Special consideration is given to the challenges facing silicon nanosphere anodes, as well as prospects and future directions that are critically addressed. The manuscript is optimistic about the future of silicon-based nanospheres in energy storage, even though it faces problems like cost, scalability, and integration into existing battery systems. The study outlines the bright prospects of silicon-based nanosphere anodes, offering insights into the path forward for advancing this technology and emphasizing their role in the sustainable development of battery technology. ? 2024 Elsevier Ltd